Total phenolics and flavonoids content in ripened and unripened fruits of different mulberry (Morus alba) varieties - KUMAR, R VENKATESH; BABU, G SUNIL; CHAUHAN, SEEMA; SRIVASTAVA, AMIT; RAO, YASHWANT; KUMAR, DHIRAJ (The Indian Journal of Agricultural Sciences, 2012)
The results of the experiment indicated that K 2 mulberry variety have shown maximum flavonoid and phenolic content in un-ripened fruits, while AR 14 variety have maximum total phenolic content in ripened fruits. The BR 2 mulberry variety has highest total flavonoids content in ripened fruits. The high contents of functional compounds in mulberry juice, fruits, and leaves implied that they might be potential resources for the development of functional drinks and food. Considering the advantages of potential medicinal properties of flavonoids and phenols enriched fruits of mulberry it can be utilized to treat several diseases of animals and human being.